Kaizen strategies to optimize the quality of drinking water and sanitation services in the hydrological company of Cojedes (Gestión y Gerencia, 2023)
This article shows the evaluation of the application of Kaizen strategies to optimize the quality of drinking water and sanitation services in the Cojedes hydrological company. The work was based on a descriptive field research, under the framework of a feasible project. The population consisted of 96 employees of this organization, the sample included 29 workers assigned to a water treatment plant, belonging to the hydrological, to whom a questionnaire was applied with a Likert-type scale, which was validated by expert’s judgment, whose reliability yielded 0.87 in Cronbach's alpha coefficient. In this sense, the results obtained were able to diagnose the affectation of the quality of the drinking water and sanitation service provided by the company under study, thus allowing to determine, design, implement and evaluate the appropriate kaizen strategies to optimize the quality of this vital service, since it involves the three guiding principles for continuous improvement: process-oriented, maintenance-oriented and individual-oriented, the latter being the best investment, taking into account training, work management and response to the challenges presented in their work. It is concluded that the water utility does not have a technical planning instrument to guide its management with respect to the portable water production process; therefore, the proposal on kaizen strategies to optimize the quality of drinking water and sanitation services in this company is very timely.
Keywords: Kaizen strategies; drinking water and quality; public policy